Fiscal Adjustment and Economic Development : A Case Study of Nova Scotia - Graham, John F. (Book collections on Project MUSE., 1963)
This study is an attempt to find a solution to the problem of fiscal adjustment between a province or a state and its municipalities taking Nova Scotia as a case study.